2018
DOI: 10.5152/tjar.2018.37929
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Endovascular Aneurysm Repair: Mortality, Myocardial Infarction and Acute Kidney Injury

Abstract: Objective: Patients undergoing endovascular aneurysm repair (EVAR) have comorbidities that increase the risk of death, myocardial infarction (MI) and acute kidney injury (AKI). Our aim was to evaluate the incidence and predictors of mortality, MI and AKI after EVAR and to compare AKI incidence with Vascular Surgery Kidney Injury Predictive Score (VSKIPS). Methods: We conducted a retrospective study of EVAR procedures performed between March 2006 and November 2013. We defined mortality at 30 days, MI as an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…69 In recent years, however, studies that have used standardized criteria for AKI have reported an incidence of AKI after EVAR for infrarenal AAA of 9%-21% (Table 4). [70][71][72][73][74][75][76][77][78][79][80][81] Open repair is associated with a 1.6-to 2-fold higher risk of AKI but better long-term preservation of kidney function 59,80,82 than EVAR. Juxtarenal, suprarenal, or thoracoabdominal aneurysms cannot be treated with standard "off the shelf " EVAR devices and require individualized fenestrated EVAR (fEVAR) or branched EVAR devices (Figure 3), which are associated with considerably higher rates of AKI.…”
Section: Aki and Egfr Decline After Aaa Surgery: Incidence And Impactmentioning
confidence: 99%
“…69 In recent years, however, studies that have used standardized criteria for AKI have reported an incidence of AKI after EVAR for infrarenal AAA of 9%-21% (Table 4). [70][71][72][73][74][75][76][77][78][79][80][81] Open repair is associated with a 1.6-to 2-fold higher risk of AKI but better long-term preservation of kidney function 59,80,82 than EVAR. Juxtarenal, suprarenal, or thoracoabdominal aneurysms cannot be treated with standard "off the shelf " EVAR devices and require individualized fenestrated EVAR (fEVAR) or branched EVAR devices (Figure 3), which are associated with considerably higher rates of AKI.…”
Section: Aki and Egfr Decline After Aaa Surgery: Incidence And Impactmentioning
confidence: 99%
“…According to the European Society of Cardiology (ESC)/European Society of Anesthesiology (ESA) guidelines, EVAR is an intermediate cardiac risk procedure, with a 1%–5% incidence of cardiac events (MI or cardiac death) [ 2 ]. In our study, all patients had ASA risk score ≥ 3 (31 patients (72.1%) had ASA-3 and 12 patients (27.9%) ASA-4).…”
Section: Discussionmentioning
confidence: 99%
“…AAA is a common disease that constitutes a serious health problem [ 1 , 2 ]. It particularly affects men older than 60 years with a prevalence that ranges from 2% to 7% [ 1 , 2 ]. In 1991, Parodi, Palmaz, and Barone reported the first EVAR for AAA [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, AKI develops in 15–20% of patients having elective EVAR for infrarenal AAA. 53 , 59–68 , 76 Whether open repair is associated with a lower, equal, or higher AKI risk is not yet clear. Saratzis et al .…”
Section: Acute Kidney Injury After Abdominal Aortic Aneurysm Surgery:...mentioning
confidence: 99%